"AVANTE GUARAPUAVA" : EDUCAÇÃO E MODERNIZAÇÃO NA DÉCADA DE 50 - Souza, Lucineia Moreira de (2014)
The modernisation process experienced by Guarapuava, in the 1950s, explains the duality exists in the region: the ancient society, formed by farmers` descendants, and emerging class social media, formed by the insertion of immigrants and migrants in the region, in the quest to make Guarapuava a modern city, matched to other cities developed in the country. Starting from this consideration, the objective of the thesis was to show that the education in Guarapuava society was not alien to modernising processes. For this reason, we believe the national developmentalism and the populist policies such as modernising aspects, which were highlighted in the year of 1950 in the whole of Brazil, increasing concerns about the schooling process, based on the principles of free, compulsory and secular education for all. For this task, we use the local newspapers circulated in the 1950s, a time that we as the source and object of study for the production of knowledge. In the first chapter we understand the processes of modernization in its historicity, as well as upgrading consisted in developmentism accelerated in underdeveloped countries. Therefore, in the 1950s, the primary education was, on the one hand, collaborative for the economic development of the country in the direction of expansion of primary education in industrialized regions, and on the other hand, the discussions regarding the right of all to education was object of political dispute. In the following chapter, we try to understand that the modernization in the State of Parana was triggered from the agriculture, being that the settlement addressed in Parana stimulated the coffee plantation, the offer of paid employment, and the composition of various social groups to 1960. In the process of modernization of the State of Parana and, specifically in Guarapuava, education began to have a sense of organizing element and originator of society with a view to economic progress, political, social and cultural, therefore the defense of schooling of children of school age has become imperative. In the last chapter, we try to show some economic changes, political, social, and educational that occurred in the 1950s in Guarapuava - PR, arguing that education was one of the subjects treated with greater intensity in the newspapers containing in the central west region of Parana and, furthermore, this was understood as an element for progress in the region. In this context, the education process of children of school age in Guarapuava, configured as a factor required for the systematization of modernising processes in this territory.